2021
DOI: 10.1021/acs.jmedchem.1c01423
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Water Networks is the Cause of Human/Mouse Species Selectivity in Urokinase Plasminogen Activator (uPA) Inhibitors Derived from Hexamethylene Amiloride (HMA)

Abstract: The serine protease urokinase plasminogen activator (uPA) plays a critical role in tumour cell invasion and migration and is a promising anti-metastasis drug target. 6-Substituted analogues of 5-N,N-(hexamethylene)amiloride (HMA) are potent uPA inhibitors that show anti-metastatic effects in vivo and high selectivity over closely related trypsin-like serine proteases, while lacking the diuretic and anti-kaliuretic properties of the parent drug amiloride. However, the compounds as a class display pronounced sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…Relative to amiloride, 6-iodoamiloride 94 shows moderately decreased ENaC activity (the K + -sparing and diuretic target of the parent drug), and modestly improved potency at the sodium–hydrogen exchanger, isoform 1 (NHE1). ,, 6-iodoamiloride has been used as a probe of Na + -mediated processes in diverse settings, including in elucidation of the mechanisms of Na + -driven bacterial flagellar motion . In addition to differing selectivity for the classical Na + -driven targets of amiloride, 94 also shows improved inhibitory activity against the uPA, a TLSP known to play roles in cancer progression and inflammatory disorders. , The enhanced activity of 94 has been attributed to enhanced occupation of the S1β subsite of the uPA proteolytic domain, a tractable amiloride pharmacophore that has been extensively characterized by multiple groups. , Furthermore, we recently published an evaluation of 94 and related analogs for activity at the trimeric ligand-gated ion channel P2X7, a key regulator of peripheral and central inflammation and known off-target of amiloride, finding no significant difference in inhibitory activity when compared to amiloride in whole-cell functional assays …”
Section: Discussionmentioning
confidence: 99%
“…Relative to amiloride, 6-iodoamiloride 94 shows moderately decreased ENaC activity (the K + -sparing and diuretic target of the parent drug), and modestly improved potency at the sodium–hydrogen exchanger, isoform 1 (NHE1). ,, 6-iodoamiloride has been used as a probe of Na + -mediated processes in diverse settings, including in elucidation of the mechanisms of Na + -driven bacterial flagellar motion . In addition to differing selectivity for the classical Na + -driven targets of amiloride, 94 also shows improved inhibitory activity against the uPA, a TLSP known to play roles in cancer progression and inflammatory disorders. , The enhanced activity of 94 has been attributed to enhanced occupation of the S1β subsite of the uPA proteolytic domain, a tractable amiloride pharmacophore that has been extensively characterized by multiple groups. , Furthermore, we recently published an evaluation of 94 and related analogs for activity at the trimeric ligand-gated ion channel P2X7, a key regulator of peripheral and central inflammation and known off-target of amiloride, finding no significant difference in inhibitory activity when compared to amiloride in whole-cell functional assays …”
Section: Discussionmentioning
confidence: 99%
“…This is a typical cut-off value for studies with MD simulations followed by MM/GBSA calculations. 21,22,[69][70][71][72][73][74] SHAKE algorithm was used to constrain bonds with hydrogen atoms, enabling the application of an integration time-step of 2 fs.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Our previous work focused on the selective optimization of the side-activities of amiloride and its analogues as anticancer agents. , It has been reported that NHE1 is among the potential targets for the observed anticancer effects of amiloride and its analogues. ,,, To begin, we constructed a three-dimensional homology model of NHE1. With the publication of a long-awaited experimental structure and our interest in developing novel NHE1 inhibitors, we subsequently conducted molecular dynamics (MD) simulations of the apo- and ligand-bound states as well as relative binding free energy perturbations (FEP) MD simulations.…”
Section: Introductionmentioning
confidence: 99%